2016
DOI: 10.3389/fpsyg.2016.01114
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Gender Beliefs in Spatial Ability: Stronger Stereotyping in Boys than Girls

Abstract: Sex differences in spatial ability are a seriously debated topic, given the importance of spatial ability for success in the fields of science, technology, engineering, and mathematics (STEM) and girls' underrepresentation in these domains. In the current study we investigated the presence of stereotypic gender beliefs on spatial ability (i.e., “spatial ability is for boys”) in 10- and 12-year-old children. We used both an explicit measure (i.e., a self-report questionnaire) and an implicit measure (i.e., a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…However, some studies revealed that, male preservice teachers had higher levels of spatial thinking skills than females, and female preservice teachers had higher levels of anxiety than male preservice teachers (Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Ramirez, Gunderson, Levine & Beilock, 2012). In addition to these studies, Vander Heyden et al revealed that children's choices for activities which require spatial thinking skills may vary by gender, but there are no statistically significant differences between boys' and girls' spatial thinking skills (Vander Heyden, van Atteveldt, Huizinga, & Jolles, 2016). The numbers of male and female participants (11 to 121) might not be enough, or there may be some other factors to be investigated related to gender as a factor influencing spatial abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies revealed that, male preservice teachers had higher levels of spatial thinking skills than females, and female preservice teachers had higher levels of anxiety than male preservice teachers (Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Ramirez, Gunderson, Levine & Beilock, 2012). In addition to these studies, Vander Heyden et al revealed that children's choices for activities which require spatial thinking skills may vary by gender, but there are no statistically significant differences between boys' and girls' spatial thinking skills (Vander Heyden, van Atteveldt, Huizinga, & Jolles, 2016). The numbers of male and female participants (11 to 121) might not be enough, or there may be some other factors to be investigated related to gender as a factor influencing spatial abilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is the reality. However, gender is being widely investigated in terms of whether it is an influential factor on spatial thinking skills or not (Abay, Tertemiz, & Gökbulut, 2018;Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Hacıömeroğlu & Hacıömeroğlu, 2017;Maiorana, 2014;Newcombe, 2013;Vander Heyden, van Atteveldt, Huizinga, & Jolles, 2016). This is why we aimed to investigate gender as a factor for prospective preschool teachers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies found that men and women were stereotypically believed to be better at spatial and verbal abilities, respectively (Halpern & Tan 2001;Hausmann, Schoofs, Rosenthal, & Jordan 2009;Hausmann 2014;Hirnstein, Coloma Andrews, & Hausmann 2014;Moè, Meneghetti, & Cadinu 2009). Already 10-to 12-year-olds believed that boys/men have better spatial (Vander Heyden, van Atteveldt, Huizinga, & Jolles 2016) and girls/women better verbal skills (Kurtz-Costes, Copping, Rowley, & Kinlaw 2014). Most of the studies on gender stereotypes in spatial and verbal abilities tested psychology students or did not specify the academic background of their sample.…”
Section: Gender Stereotypes and Ability Related Beliefsmentioning
confidence: 99%
“…spatial perspective taking [17]). Intrinsic abilities emerge around the age of four, whereas extrinsic dynamic abilities are detectible later in the development, becoming dissociated around the age of 9 to 10 years, at which point intrinsic spatial ability matures into an adult form [18]. However, in all of these the focus is on spatial configurations; even in dynamic tasks, there is no concern with the temporal dimension, merely with initial and final states.…”
Section: Spatial and Spatial-temporal Cognitionmentioning
confidence: 99%